The Form of The Presidential System in Indonesia: A Comparative Study of Several Countries - Sumerta Yasa, Putu Gede Arya (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2021)
The purpose of this research is to determine how the form of the presidential system adopted by Indonesia and to compare the presidential system in Indonesia with several countries such as the United States, South Korea and the Philippines. The research method used in this study is a normative legal research which used statute approach, conceptual approach, and comparative approach to examine the vacuum of norm regarding the presidential system in Indonesia. The results show that Indonesia adheres to non pure presidential system, namely a quasi-presidential system which is indicated by the horizontal relationship between state institutions. In the implementation of the presidential government system, every country has different characteristics so that it undergoes modifications depending on the situation and conditions of the country that adheres to it. When Indonesian presidential system compared with the United States, South Korea and the Philippines, it will show the special characteristics and weaknesses of each country. The indicators used in comparing presidential systems in several countries are the form of the presidential system, special characteristics, and weaknesses which in general are excess power in the executive.